Characteristics of Starch-Based Carbon Foams Filled with Zeolite and Activated Carbon - Mohd Zaki, Wan Nazirafazlin; Mohamed Hatta, Mohamed Nasrul (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This study investigates the development of starch-based carbon foam composites enhanced with zeolite and activated carbon fillers to improve structural, mechanical and absorption properties for sustainable material applications. This research addresses the environmental challenges of fossil fuel-based materials and aims to produce environmentally friendly alternatives using renewable tapioca starch. A systematic methodology was adopted, starting with preparing samples containing various concentrations of zeolite and activated carbon (0%, 2%, 4%, 6%, and 8%). The process involved mixing, drying and carbonization at 800°C, followed by extensive characterization using density and porosity tests, compression tests, Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR), and carbon dioxide absorption analysis. The results showed that increasing the filler content increased the density, reduced the porosity and increased the compressive strength. The zeolite filler was more effective in reducing porosity and increasing the density, while the activated carbon filler exhibited superior mechanical strength and stress distribution due to its better compatibility with the starch matrix. SEM and FTIR analyses confirmed the structural and chemical changes, highlighting the stronger bonding of the activated carbon with the matrix. Both fillers increased the carbon dioxide absorption capacity, with zeolite showing a higher absorption rate at a concentration of 6%. These findings underline the potential of these composites for environmental applications, especially in CO₂ capture and storage. In conclusion, this study provides insights for optimizing the filler concentration to tailor the material properties for specific applications, advancing sustainable materials for green technologies. Future work should explore thermal insulation, electrical conductivity, and chemical stability for broader applications.